Analisis Perencanaan Prosedur Audit Laporan Keuangan pada Kantor Akuntan Publik XYZ - Joice Irene Priskila; Dimaz Ramananda (Al-Buhuts, 2025)
This research aims to analyze the procedures of the planning financial audit conducted by KAP XYZ. The basis to analyze every step in the procedures of the planning financial audit is according to the Standards on Auditing in the Professional Standards of Certified Public Accountants (SPAP) set by the Institute of Certified Public Accountants Indonesia (IAPI). Audit procedures is a tool to increase the quality of audited financial statement. The author used qualitative descriptive by doing a direct interview and observation at the place of KAP XYZ. Based on the interview and discussion result, the author indicate that some of the procedures of planning financial audit conducted by KAP XYZ are not yet in accordance and some of the procedures of planning finansial audit are in accordance to the procedures of planning financial audit by SPAP.